The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/mjt.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Advances in the Management of Cardiogenic Shock

Abstract: Background: Cardiogenic shock (CS) is a life-threatening state of tissue hypoperfusion, associated to a very high risk of mortality, despite intensive monitoring and modern treatment modalities. Present review aims to describe the therapeutic advances in the management of CS. Areas of Uncertainty: Many uncertainties about CS management remain in clinical practice, and these relate to intensity of invasive monitoring, the type and timing of vasoactive therapies, the risk-benefit ratio of mechanical circulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 92 publications
(105 reference statements)
1
28
0
Order By: Relevance
“…Legend: The cut-off value was set at 62 h, prediction sensitivity was 92.3%, and specificity was 65.6%. tIPPaO2, time of inflection point of arterial oxygen partial pressure cautiously recommended as an alternative option for CA/RCS [1,4,10,14]. The present study showed an overall survival rate similar to that in previous studies [10,12,15].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Legend: The cut-off value was set at 62 h, prediction sensitivity was 92.3%, and specificity was 65.6%. tIPPaO2, time of inflection point of arterial oxygen partial pressure cautiously recommended as an alternative option for CA/RCS [1,4,10,14]. The present study showed an overall survival rate similar to that in previous studies [10,12,15].…”
Section: Discussionsupporting
confidence: 87%
“…Reportedly, traditional CPR therapy survival rate for in-hospital CA is between 35.6 and 39.7% and between 7.7 and 8.3% for out-of-hospital CA [ 7 , 11 ]. RCS mortality rate is also high at 30–60% [ 10 ] Multi-center prospective RCT studies are still lacking because multiple factors affect the VA-ECMO treatment prognosis and complex ethical issues are involved in the process. However, a few studies, such as ARREST trial [ 12 ], show that CA/RCS patients treated with VA-ECMO might improve survival compared with traditional treatment [ 5 , 7 , 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CS may be caused by a variety of cardiovascular conditions, the most common reason is STEMI (15). Although there have been great improvements in pharmacological treatment and reperfusion therapy of patients with CS in the last two decades, the mortality rate among these patients still remains to be high (16). Additionally, this condition is frequently complicated with the deterioration of renal functions that has been related with further increase in mortality rates (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of early coronary revascularization and the advances in cardiogenic shock treatment, the inability to rapidly restore regional tissular normoxia represents a critical factor impacting MI prognosis ( 2 ). Monitoring, as early as possible, organ-specific dynamics of hypoxia represents a candidate strategy to guide treatments and to timely identify high-risk patients ( 3 ). Currently, serum biomarkers like lactate are used to gauge global tissue perfusion.…”
Section: Introductionmentioning
confidence: 99%